(untitled) (REMUNOM, 2023)
The routine of dental care is marked by a number of factors and among them are the fear and anxiety of patients, especially those who are seeking care for the first time. Fear is characterized as the fear of threatening attitudes or activities of external origin that keep the individual in a state of distress; and anxiety promotes a more lasting state of tension in patients in the face of invasive treatments or even previous experiences and reports from other people. The aim of this study was to investigate patients’ fear and anxiety about dental care at the dental school clinic of the Federal University of Campina Grande, Patos/PB. The study was observational, quantitative, analytical and cross-sectional, with a convenience and representative, sample of 132 patients seen at the CEO. For data collection, research questionnaires were used to investigate the patients’ fear (Gatchel Fear Scale) and anxiety (Modified Dental Anxiety Scale - MDAS) and a sociodemographic questionnaire. The data was evaluated using the statistical program Statistical Package for Social Sciences and descriptive and inferential bivariate statistical techniques were used to analyze it. Of those interviewed, 63.3% were female, the majority (53.8%) were aged between 18 and 40, had a monthly income of between 1 and 2 minimum wages (84.1%) and 56.1% had completed high school. Regarding their behavior towards dental care, 72.7% never avoided treatment and 90.2% never missed appointments. Patients said that they felt relaxed in the following situations: 63.6% when they had to go to the dentist, 66.7% while waiting in the waiting room, 56.8% when using the "dental motor", 63.6% when having their teeth scraped and 54.5% in relation to anesthesia. Of the sample, 119 (90%) patients were considered not to be anxious. When asked if they were afraid of dental treatment, 51.5% said they were not afraid. It was also possible to verify a statistically significant association (p=0.049) between the level of fear and age group and between the level of anxiety and fear (p=0.001), but there was no statistical significance between the level of anxiety and the patients’ sociodemographic data. It is concluded that the majority of patients are not afraid, they feel relaxed with dental care, characterizing themselves as not anxious.